Estudo químico e avaliação biológica dos alcaloides presentes em Erythrina mulungu (Fabaceae) - Cavallieri, Karina (2019)
Species of the genus Erythrina have been shown alkaloids with diverse pharmacological properties, including sedative, anti-hypertensive, hypnoti, bactericidal and fungicidal. Erythrina mulungu, known as mulungu, is a native species of the Cerrado and used in folk medicine for insomnia, depression and sedative. Reports in the literature about extracts and metabolites of E. mulungu motivated us to a study towards the alkaloids present in the stem bark. Thus, was prepared the ethanolic extract submitted to liquid-liquid extraction with hexano, CH2Cl2 and AcOEt. The fractions were evaluated by thin layer chromatography and revealed with iodochloroplatinate to identify the higher concentration of alkaloids in the fraction CH2Cl2. This fraction was submitted to different chromatographic procedures, such as column chromatography (CC), hight performance liquid chromatography and preparative thin layer chromatography, which resulted in the isolation of the alkaloid erysotrine (II). Analysis by ultra-high-performance liquid chromatography–electrospray ionization high-resolution tandem mass spectrometry allowed the identification of the erysotramidine (I). The ethanolic extract was also subjected to acid-base extraction, from which the alkaloidal fraction AcOEt was obtained. This fraction was subjected to CC from which erysotrine N-oxide (III) was isolated. The structures were elucidated by the spectroscopic (mono- and bi-dimensional nuclear magnetic resonances, and ultraviolet) and sprectrometric (mass spectrometry) techniques. Thus, the ethanolic extract, fraction CH2Cl2, EtOAc alkaloidal fraction, and alkaloids II and III were submitted to the in vitro anticholinesterase assay. Further, compound II exhibited similar inhibitory activities for AChE (IC50 1236.1 ± 173.2 µM) and BChE (IC50 1011.8 ± 101.7 µM), as well the alkaloid III (IC50 1234.7 ± 192.4 and 1235.0 ± 39.1 µM). These results demonstrated that the isolated compounds have low inhibitory activity when compared with the positive control galantamine (IC50 5.0 ± 0.3 e 162.7 ± 28.8 µM). The ethanolic extract and the CH2Cl2 fraction presented low inhibition potential of the enzymes, whereas the AcOEt alkaloid fraction showed no inhibitory activity for both AChE and BChE within the evaluated range of concentration.